Critical overview of the main features and techniques used for the evaluation of the clinical applicability of L-asparaginase as a biopharmaceutical to treat blood cancer. (September 2020) - Costa-Silva, T.A.; Costa, I.M.; Biasoto, H.P.; Lima, G.M.; Silva, C.; Pessoa, A.; Monteiro, G.
Abstract: L-asparaginase is an enzyme used as a biopharmaceutical to treat acute lymphoblastic leukemia. Several adverse effects have been related to L-asparaginase use, so the scientific community has searched for novel proteoforms of L-ASNase. However, some critical characteristics must be considered for a novel L-ASNase source to be effective as an antitumour drug. Accordingly, this article provides a critical analysis of the parameters and methods applied to estimate L-ASNase concentration, measure the L-ASNase and GLNase activities and kinetics, evaluate the enzyme preparations purity and define the antitumour activity against leukemic cells in vitro. Among the main features, the proposed new enzyme needs to present high affinity for L-asparagine; low percentage of glutaminase activity in relation to L-ASNase; high enzyme stability and half-life and mainly antileukemic activity when a low protein amount is applied. These parameters are discussed in an attempt to guide the consideration of an enzyme as a promising biopharmaceutical against ALL.